2012
DOI: 10.1088/1478-3975/10/1/016001
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic stretch reveals a mechanical role for intermediate filaments in a desminopathic cell model

Abstract: Mechanics is now recognized as crucial in cell function. To date, the mechanical properties of cells have been inferred from experiments which investigate the roles of actin and microtubules ignoring the intermediate filaments (IFs) contribution. Here, we analyse myoblasts behaviour in the context of myofibrillar myopathy resulting from p.D399Y desmin mutation which disorganizes the desmin IF network in muscle cells. We compare the response of myoblasts expressing either mutated or wild-type desmin to cyclic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…This seemed to be consistent with an earlier observation that microtubules disruption apparently had little effect on the elastic moduli of myoblasts measured using atomic force microscopy (AFM) (Collinsworth et al 2002). Intermediate filaments seemed to play significant roles when cells were being stretched (Leccia et al 2013) and under large deformation (Wang and Stamenovic 2000).…”
Section: Introductionsupporting
confidence: 90%
“…This seemed to be consistent with an earlier observation that microtubules disruption apparently had little effect on the elastic moduli of myoblasts measured using atomic force microscopy (AFM) (Collinsworth et al 2002). Intermediate filaments seemed to play significant roles when cells were being stretched (Leccia et al 2013) and under large deformation (Wang and Stamenovic 2000).…”
Section: Introductionsupporting
confidence: 90%
“…Cell stretching is supposed to mimic muscle contraction/shrinkage. Here, stretching conditions of 20% elongation and 6 hours’ duration were based on previous experiments on cell reorientation dynamics [29]. Other authors found increased cell death and substrate detachment with 30% elongation and similar frequency [23].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were stretched as described previously [29]. Briefly, cells were plated on elastomeric strips of poly-dimethylsiloxane (PDMS) (Sylgard 184, Corning) coated with fibronectin (Sigma-Aldrich) at 2 x 10 3  cells/cm 2 and cultured for 72 h before stretching.…”
Section: Methodsmentioning
confidence: 99%
“…To begin to understand intercytoskeletal communications, we focused on muscle desmin and actin, which are involved in force‐related events and in the scaffolding of the complex muscle architecture (Charrier et al, ; Leccia et al, ; Palmisano et al, ). The interaction of desmin filaments with muscle proteins of nebulin and nebulette contributes to the organization of the Z‐disk structure, and the modulation of their affinity by desmin mutations can induce dysfunction of striated muscle cells (Baker et al, ; Hernandez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To begin to understand intercytoskeletal communications, we focused on muscle desmin and actin, which are involved in forcerelated events and in the scaffolding of the complex muscle architecture (Charrier et al, 2016;Leccia et al, 2012;Palmisano et al, 2015).…”
mentioning
confidence: 99%